1989
DOI: 10.1073/pnas.86.6.2013
|View full text |Cite
|
Sign up to set email alerts
|

A general native-state method for determination of proliferation capacity of human normal and tumor tissues in vitro.

Abstract: An important need in cancer research and treatment is a physiological means in vitro by which to assess the proliferation capacity of human tumors and corresponding normal tissue for comparison. We have recently developed a native-state, three-dimensional, gel-supported primary culture system that allows every type of human cancer to grow in vitro at more than 90% frequency, with maintenance of tissue architecture, tumor-stromal interaction, and differentiated functions. Here we demonstrate that the native-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The brightgreen nuclear staining is due to silver grains being exposed due to [3H]thymidine incorporation. The polarized light is then reflected as bright green (30). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The brightgreen nuclear staining is due to silver grains being exposed due to [3H]thymidine incorporation. The polarized light is then reflected as bright green (30). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The slides were then analyzed with a polarizing microscope at x 400 power in a blinded fashion (30). Replicating cells were easily determined by the presence of bright-green-reflecting silver grains over the cell nuclei.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26) A histoculture method was developed by modifying a tissue culture method to make it three-dimensional with similar use of ECM, and employed for long-term culture of primary tumor cells. [27][28][29] Using this culture method, Hoffman et al 30) and Furukawa et al established the histoculture drug response assay (HDRA), and have reported its clinical utility. [31][32][33] However, in their method, the concentration of the applied drug was tens or hundreds of times higher when converted to AUC, whereas in CD-DST, the concentration of the applied drug is close to the in vivo level, which appears to be more reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Briefly, each tumor specimen was minced finely and aseptically with a scalpel, which was then placed on each of the prepared collagen surfaces in 24-well plates. The plates were incubated at 37 C for 7 days with the drug dissolved in RPMI 1640 medium containing 20% fetal calf serum in a…”
Section: Quantification Of Apoptotic Cells In Tissue Sectionsmentioning
confidence: 99%